(untitled) (International Journal of Engineering and Computer Science, 2021)
Technological convergence among communication, computing, and control systems is expected to result in a wide range of novel industrial solutions with more intelligence, lower cost, and better sustainability traits that are difficult or even impossible to achieve using the three system types independently. This paper focuses on conveying the system-level reliability definition and quantification towards a ubiquitous convergence of the three practical systems. Related key arguments are made, together with research opportunities and hotspots. Technological convergence is defined as the integration of two or more distinct technologies into a unified system or product. By the universal convergence of communication, computing, and control, a wide range of novel Internet of Things (IoT) solutions is expected. The three systems would not only be packaged together, but all processed and communicated without boundaries. The convergence-enabled systems can be deployed more compactly, enable a wider range of applications, and respond to events even faster. The convergence offers many opportunities to facilitate the achievement of better intelligence, lower cost, and better sustainability traits, but also confronts many challenges. The next generation cellular communication systems have developed into research hotspots to support more complex and diversified applications with ultra-high reliability, high-density terminals, low-latency communication, reduced energy consumption, and full-spectrum coverage. With the rapid evolution of wireless technology, sensing and actuation devices have become lower-cost, smaller, more intelligent with artificial intelligence capacities, and hence readily integrated for development into compact cyber-physical systems (CPS). New applications of CPS such as autonomous driving and manufacturing are emerging. The unprecedented integration of terminals changes communication and control requirements. Multi-domain systems need to communicate, process, and control information from different types and dimensions. A cross-domain paradigm becomes necessary to effect a rapid performance response. It is expected that the convergence-nature behavior would bring novel automation and IoT solutions that are more intelligent, lower cost, and better sustainable. However, highly complex systems would preferably result in unpredictable and unreliable solutions that are hard to be tested, validated, and certified.